Multiobjective optimization on CI engine performance and emissions fueled with croton macrostachyus (CMS) seed oil biodiesel blends employing the desirability approach - Adem Siraj Mohammed; Venkata Ramayya Ancha; Samson Mekbib Atnaw (Results in Engineering)
This experimental study examined the combined effects of injection timing (26, 27, and 28 °CA), biodiesel blend ratio (B0-B25), and engine speed (1700–2900 RPM) on the performance (BTE, BSFC) and emissions (NOx, CO2) of a single-cylinder CI engine fueled with croton macrostachyus (CMS) seed oil methyl ester. Using a central composite design (CCD), key parameters were varied, and responses measured, followed by a desirability-based multi-objective optimization. The regression’s fit statistics were computed using R2 values of 86.15 %, 83.42 %, 91.03 %, and 80.31 % for the response parameters of BTE, BSFC, NOx, and CO2, respectively. The result revealed that advancing the injection timing resulted in a highest BTE of 31 %, a reduced BSFC by 42.85 %, a 19.06 % NOx reduction, an increase in CO2 emission at higher biodiesel blending ratios, and lower engine speed. When increasing the engine speed from 1700 to 2900 RPM, the BSFC was increased by 27.3 %, and the NOx was reduced by up to 44.4 % at higher blending ratios. The reason could be that at higher engine speeds, the time available for each combustion cycle is reduced, which can lead to incomplete combustion and lower thermal efficiency. The multi-objective optimization identified optimal settings (B22.6 blend, 28 °CA timing, 2306 RPM) that provided a balance, achieving 28.02 % BTE, 0.471 kg/kWh BSFC, 35 ppm NOx, and 4.6 % Vol. CO2. Utilizing a higher biodiesel blending ratio at advanced injection timing and optimal engine speed range is the best way to achieve enhanced engine performance and reduced NOx emissions.